Miguel Querol Gavaldá, La música en las obras de Cervantes, Ediciones Comtalia, Barcelona, 1948. 173 págs. - Sálazar, Adolfo (El Colegio de México, 2007)
Se reseñó el libro: La música en las obras de Cervantes